T follicular helper cells in the humoral immune response to SARS-CoV-2 infection and vaccination. Issue 2 (3rd November 2021) - Koutsakos, Marios; Lee, Wen Shi; Wheatley, Adam K; Kent, Stephen J; Juno, Jennifer A
Abstract: Vaccination remains the most effective mechanism to reduce the impact of COVID-19. Induction of neutralizing antibodies is a strong correlate of protection from infection and severe disease. An understanding of the cellular events that underpin the generation of effective neutralizing antibodies is therefore key to the development of efficacious vaccines that target emerging variants of concern. Analysis of the immune response to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and vaccination has identified circulating T follicular helper cells (cTFH ) as a robust correlate of the neutralizing antibody response. Here, we discuss the analysis of cTFH cells and their lymphoid counterparts in human humoral immune responses during COVID-19, and in response to vaccination with SARS-CoV-2 spike. We discuss the phenotypic heterogeneity of cTFH cells and the utility of cTFH subsets as informative biomarkers for development of humoral immunity. We posit that the analysis of the most effective cTFH will be critical to inducing durable immunity to new variants of SARS-CoV-2. Graphical Abstract: Review on the analysis of TFH cells during COVID-19 infection and vaccination and the role of these cells as biomarkers of neutralising antibody development.